A Study of Co-Micronization In Formulation of Rapid Dispersible Tablets: Impact of Micronization and Co-Micronization on Formulation of Rapid Dispersible Tablets (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The concept of rapid dispersible, fast dissolving, quick dissolving, and Orodispersible tabletsdosage forms have acquired great importance in recent years due to their unique properties andadvantages over other available dosage forms. The micronization of TA and diluents was done by usingAir-jet mill. The comicronization of formulation was done as per the given details in table. Total threecycle of micronization was completed to insure the proper particle size reduction of blend. There is nomicronization of formulation F-1 was done; it was basically used as reference to check the impact ofmicronization and co-micronization. But sifting of Tolfenamic acid (non-micronized) of Formulation F-1was done through #60 meshes to insure the uniformity of Tolfenamic acid in blend. The micronization ofTA and diluents was done by using Air-jet mill. The comicronization of formulation was done as per thegiven details in table. Total three cycle of micronization was completed to insure the proper particle sizereduction of blend. There is no micronization of formulation F-1 was done; it was basically used asreference to check the impact of micronization and co-micronization. But sifting of Tolfenamic acid (nonmicronized)of Formulation F-1 was done through #60 meshes to insure the uniformity of Tolfenamic acidin blend.